Efficacy analysis of endovascular treatment for ruptured internal carotid artery pseudoaneurysm hemorrhage in patients with nasopharyngeal carcinoma after radiotherapy - Lin, Zhipeng; Zou, Xugong; Chen, Yuan; Li, Xiaoqun; Zhang, Jian; Huang, Dabei (Frontiers in Surgery, 2024)
Background: To evaluate the efficacy and complications of endovascular treatment for hemorrhage caused by ruptured internal carotid artery pseudoaneurysms following radiotherapy in nasopharyngeal carcinoma (NPC) patients. Methods: To retrospectively analyze NPC patients who underwent endovascular treatment for ruptured internal carotid artery pseudoaneurysm hemorrhage after radiotherapy at Zhongshan People's Hospital from January 2016 to December 2022. The study aims to assess the postoperative hemostasis rate, postoperative rebleeding rate, complication rate, and 1-year postoperative survival rate. Results: During the study period, 36 patients underwent endovascular treatment, of which 24 patients underwent embolization of the internal carotid artery and 12 patients underwent stenting of the internal carotid artery. The procedure success rate was 100%. The rebleeding rate at 1 year after the procedure was 5.6% (2/36, 1 patient with stent placement and 1 patient with coil embolization), and the complication rate was 11.1% (4/36, 4 patients with coil embolization patients). Two patients developed large-area cerebral infarction after procedure, and 2 patients had different degrees of neurological impairment after the procedure. The 1-year survival rate was 91.7%(33/36). Conclusion: Ruptured internal carotid artery pseudoaneurysm hemorrhage after radiotherapy is rare but life-threatening. Endovascular treatment with coil occlusion or stenting reconstruction of the internal carotid artery provides immediate hemostasis and elimination of the pseudoaneurysm with a low rate of recurrence, which may be effective in reducing patient mortality.